Aging Is Associated With Multidirectional Changes in Social Cognition: Findings From an Adult Life-Span Sample Ranging From 18 to 101 Years. (19th August 2022) - Grainger, Sarah A; Crawford, John D; Riches, Julia C; Kochan, Nicole A; Chander, Russell J; Mather, Karen A; Sachdev, Perminder S; Henry, Julie D
Abstract: Objectives: Normal adult aging is associated with changes in social cognition. Although 4 social cognitive domains have been identified (social perception, theory of mind [ToM], affective empathy, and social behavior), no study has tested all 4 domains concurrently in a life-span sample, limiting understanding of the relative magnitude of age-related changes across domains. This study addresses this gap by providing the first assessment of all 4 social cognitive domains in an adult life-span sample. Methods: Three hundred and seventy-two participants ranging from 18 to 101 years of age took part in this study. Participants completed a testing battery that assessed social perception, ToM, affective empathy, and social behavior, as well as broader cognitive function and well-being. Results: The results showed that adult aging is associated with multidirectional changes in social cognitive abilities, with ToM and social perception showing nonlinear decline across much of the life-span, and affective empathy and social behavior showing improvement. Age remained a significant predictor of all 4 social cognitive domains, even after accounting for broader cognitive function. Weak associations emerged between some of the social cognitive abilities and and indices of broader well-being. Discussion: These findings provide novel and important evidence that normative aging is associated with both gains and losses in social cognition that occur at distinct points of the adult life-span, and that are at least partially independent of general age-related cognitive decline.